2019
DOI: 10.3390/ijerph16152749
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Food Insecurity, Hunger and Risky Food Acquisition Practices: A Cross-Sectional Study of Food Charity Recipients in an Australian Capital City

Abstract: Inadequate social protection, stagnant wages, unemployment, and homelessness are associated with Australian household food insecurity. Little is known about the recipients of food charity and whether their needs are being met. This cross-sectional study of 101 food charity recipients in Perth, Western Australia, measured food security, weight status, sociodemographic characteristics and food acquisition practices. Seventy-nine percent were male, aged 21–79 years, 90% were unemployed, 87% received social assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…A final finding of importance is that in spite of a small proportion of patients incurring expenses related to HTN dietary requirements, the amount spent by the ones that do so is high on average and a main driver of catastrophic health expenditure, in particular in the lowest socioeconomic quintile. This is in line with evidence that healthier dietary patterns entail cost about 1.50 USD per person a day higher than the least healthy ones [47] and that food insecurity primarily affects people living on stagnant wages in poor urban communities [48,49]. Our findings highlight the vulnerability of the most deprived urban households, for whom even modest expenses to comply with medical dietary prescriptions can lead to financial hardship.…”
Section: Discussionsupporting
confidence: 89%
“…A final finding of importance is that in spite of a small proportion of patients incurring expenses related to HTN dietary requirements, the amount spent by the ones that do so is high on average and a main driver of catastrophic health expenditure, in particular in the lowest socioeconomic quintile. This is in line with evidence that healthier dietary patterns entail cost about 1.50 USD per person a day higher than the least healthy ones [47] and that food insecurity primarily affects people living on stagnant wages in poor urban communities [48,49]. Our findings highlight the vulnerability of the most deprived urban households, for whom even modest expenses to comply with medical dietary prescriptions can lead to financial hardship.…”
Section: Discussionsupporting
confidence: 89%
“…Economic access to nutritious food was highlighted as a key barrier to food security, hence the core part of this structural level initiative would ensure that all citizens have a 'right to food', achieved through the provision of an adequate living wage [8]. This study provides further evidence on the need for structural-level initiatives, such as increased government assistance, higher welfare payments (particularly Newstart in Australia), and regulations that create healthier and more affordable food environments for all [8,9,60].…”
Section: Implications For Policymentioning
confidence: 76%
“…However, the qualitative data revealed that lack of economic access due to the price and affordability of foods remained a key barrier to food security. This is not surprising, as most interviewees (58.8%) reported very low income levels, relying on ≤AUD $575 per week, compared to the average weekly wage of approximately AUD $1250 in 2019 in Australia [60]. Recent studies have estimated that, for a low-income household to meet the Australian Dietary Guidelines, they would need to spend 30% to 70% of their budget on fruits, vegetables, and healthy food items [9,61,62].…”
Section: Barriers and Enablers To Food Securitymentioning
confidence: 94%
See 1 more Smart Citation
“…While the reliance on quantitative methods has allowed for the collection of statistics on the phenomenon, it does not allow for an understanding of the lived experience of using or relying on food aid. Importantly, some of the work that has been conducted on the role of the Australian food aid sector suggests that the sector is changing, with long‐term provision of food assistance increasingly becoming entrenched in the Australian social support network (Lindberg et al., 2015; McKay & McKenzie, 2017; Pollard et al., 2019), mirroring the trajectory of the United Kingdom and Canada. The fundamental shift in the role and responsibility of the Australian food aid sector (McKay & Lindberg, 2019), means that Australian academics and policy makers many not have sufficient information about the current experiences of those accessing food aid.…”
Section: Introductionmentioning
confidence: 99%